Social Marketing Campaign through a Three-Pile Sorting Game for Bullying Prevention among Elementary School Students - Rohmadtika Dita; Cholifah; Ahmad Meidzal Syauqii (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
Bullying in elementary schools is a serious problem that impacts children's psychological and social development. The community service activity packaged under the title